Evaluation of the Metabolic Effects of Hydrogen Sulfide on the Development of Bombyx mori (Lepidoptera: Bombycidae), Using Liquid Chromatography-Mass Spectrometry-Based Metabolomics. Issue 2 (14th March 2020) - Cao, Yu-Yao; Peng, Li-Li; Jiang, Li; Thakur, Kiran; Hu, Fei; Tang, Shun-Ming; Wei, Zhao-Jun
Abstract: Hydrogen sulfide (H2 S) is a highly poisonous gas with an unpleasant smell of rotten eggs. Previous studies of H2 S have primarily focused on its effects on mammalian nervous and respiratory systems. In this study, silkworm developmental parameters and changes in metabolites in response to H2 S exposure were investigated using a hemolymph metabolomic approach, based on liquid chromatography–mass spectrometry (LC-MS). The developmental parameters, body weight, cocoon weight, cocoon shell weight, and cocoon shell ratio, were noticeably increased following H2 S exposure, with the greatest effects observed at 7.5-μM H2 S. Metabolites upregulated under H2 S exposure (7.5 μM) were related to inflammation, and included (6 Z, 9 Z, 12 Z )-octadecatrienoic acid, choline phosphate, and malic acid, while hexadecanoic acid was downregulated. Identified metabolites were involved in biological processes, including pyrimidine, purine, and fatty acid metabolism, which are likely to affect silk gland function. These results demonstrate that H2 S is beneficial to silkworm development and alters metabolic pathways related to spinning function and inflammation. The present study provides new information regarding the potential functions of H2 S in insects and metabolic pathways related to this phenomenon.